The Lexical Loan and Its Adaptation in the Spanish of the Northern Highlands of Peru: A Linguistic and Cultural Phenomenon - Cuba Manrique, María del Carmen (2020)
The topic deals with the loans from Culle and Quechua to Spanish, not only as a phenomenon of a linguistic nature but also as an element of cultural penetration that manifests itself as a sign of identity of an idiomatic community in the northern highlands of Peru, where successively and in chronological order, Culle, Inca and Hispanic societies have developed their cultures and languages. The points are developed: linguistic contact, lexical loan, linguistic adaptation of lexical loans from Culle and Quechua to Spanish, and lexical loan as a cultural phenomenon.